15 Jahre christlicher Frauenbewegung : 10 Jahre kirchl.-soz. Frauenarbeit in Berlin. Arbeitsplan der 7. Kommission : Zur Feier des 10jährigen Bestehens der 7. Arbeitskommission (zur Lösung der Frauenfrage) und des 10jährigen Bestehens der Berliner kirchl.-soz. Frauengruppe - Knebel Doebertiz, Elisabeth von (Historische Quellen zur Frauenbewegung und Geschlechterproblematik ;, 1909)
Lecture delivered at the main meeting of the Christian Social Conference on April 9, 1909 in Berlin. It is supplemented by a shorter report by Fanny von Ollech on 10 years of philanthropic work by Christian women's organizations in Berlin and by a work plan submitted by one of the groups at the conference.